2017
DOI: 10.1007/s00170-017-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of hole-making performance by coated and uncoated WC/Co cutters in helical milling of Ti/CFRP stacks

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights.Take down policy The Research Portal is Queen's institutional repository that provides access to Queen's research output. Every effort has been made to ensure that content in the Research Portal does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…For the holes made with tool T1, the difference of Ra values between hole number 60 and number 1 is 2.96 µm, whereas for the holes made with tool T2, the difference of Ra values between hole number 60 and number 1 is 4.62 µm. As identical cutting conditions were employed with both tools, the Ra difference can be related to the different wear level of the tool cutting-edge [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the holes made with tool T1, the difference of Ra values between hole number 60 and number 1 is 2.96 µm, whereas for the holes made with tool T2, the difference of Ra values between hole number 60 and number 1 is 4.62 µm. As identical cutting conditions were employed with both tools, the Ra difference can be related to the different wear level of the tool cutting-edge [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hole diameter values were closer to the nominal diameter with the T1 uncoated cutting tool compared to the coated tools because T1 had a sharper cutting edge than the other two [40]. Li et al reported that, in the drilling CFRP, the uncoated tool performed closer to the nominal diameter value compared to multilayered TiAlN+AlCrN-and TiN-coated tools and that this did not change with the increasing number of holes [41]. Similarly, Kim et al reported a higher mean diameter value with coated drills compared to uncoated drills [42].…”
Section: Evaluation Of Dimensional Accuracymentioning
confidence: 90%
“…The first one is that the cutting speed of the drilling center is zero, which may lead to adverse situations like dimensional deviation and tool deflection of holes drilled through larger thrust cutting force [1]. The second problem is the formation of exit burrs in the holes as a result of plastic deformation of workpiece materials and the geometry of cutting tool [2]. As an emerging holemaking technology, helical milling can achieve high accuracy and quality which has been extensively used to manufacture parts in aerospace industry.…”
Section: Introductionmentioning
confidence: 99%